Sleep Disorders vs. Headache: Who is the Villain? - Pereira, Diuliane Teixeira; Almeida, Ruanis Anastácio de; Bezerra, Diogo Alves Peres; Piloni, Bianca dos Anjos; Almeida, Luan Lopes da Silva; Dantas, Kaline Santos; Nunes, Antonio Jakeulmo; Santos, Ana Emília Martins dos; Filho, João Otávio Medeiros Araújo; Almeida, Allana Lopes da Silva; Santos, Késley Thuanya Fontenele dos; Faheina, Lucas Ribeiro Fernandes (Headache Medicine, 2023)
Full abstract in PDF.